DOP28 Aconitate decarboxylase 1 (ACOD1) represents a crucial regulator of monocyte recruitment, survival and proinflammatory status in intestinal inflammation. (30th January 2023) - Jones, G R; Hegarty, L; T'Jonck, W; Adams, C; Drury, B; Byrne, A; Ho, G T; Bain, C
Abstract: Background: Aconitate decarboxylase 1 (ACOD1; also known as IRG-1) is the ubiquitous source of itaconate, which dampens inflammasome activation by preventing HIF1a production of IL-1b and prevents TNF production through NRF2 activation. We reasoned that expression of ACOD1 is an inhibitory pathway within monocytes to curtail their inflammatory function, which could be manipulated in IBD therapy. Methods: We performed single-cell RNA sequencing of monocytes from colonoscopic biopsies of treatment naïve IBD patients, as well as complementary analysis of DSS treated C57BL/6J (WT) mice, using single-cell protein-mRNA (Primeflow) technologies for validation. To determine the role of ACOD1 in colitis, Acod1–/– mice were administered 2% DSS in drinking water for 6 days (acute colitis) or 4 days followed by 14 day recovery period (inflammation resolution) and assessed the colon myeloid compartment by multi-parameter flow cytometry. This was complemented with competitive bone marrow chimeric mice to assess the intrinsic role of ACOD1 controlling monocyte survival and proinflammatory status. Transcriptional profiling (Nanostring) was used to determine the molecular pathways influenced by ACOD1. Results: We found that ACOD1/Acod1 represented an evolutionarily conserved of feature of inflammation-associated monocytes, with expression present in mucosal but not blood monocytes. Acod1–/– mice demonstrated increased susceptibility to acute intestinal injury with DSS compared to co-housed WT controls, characterised by increased weight loss and colon shortening with significant accumulation of colonic neutrophils and CD64 + Ly6C + MHC-II +/ – monocytes. Consistent with Acod1 limiting inflammasome activation, Acod1–/– monocytes demonstrated significantly greater IL-1b producing capabilities than WT controls. To assess Acod1 deficient and sufficient haemopoietic cells in in the same environment, we generated competitive bone marrow chimeric mice. Acod1 deficiency conferred a significant advantage to monocyte recruitment to the colon, characterised by a 10fold increase in Ly6C + MHC-II – colon monocytes in colitis. Transcriptional profiling of WT and Acod1–/– colonic monocytes revealed significantly greater expression of molecules required for monocyte extravasation, including Sell (CD62L), Icam1, Ccr2 and Itgal (CD11a). In addition, expression of genes indicative of macrophage maturation such as Itgax (CD11c), Cd163 and Cx3cr1 were lower in the context of Acod1 deficiency, suggesting that normal maturation of these cells may be perturbed by loss of Acod1 . Conclusion: ACOD1/Acod1 represents an evolutionarily conserved, monocyte specific immuno-metabolic pathway that acts to limit monocyte recruitment, fate and pro-inflammatory function within the inflamed intestine.